Programming Human and Software-Based Web Services. - Schall, Daniel; Dustdar, Schahram; Blake, M. Brian (Computer (00189162), 2010)
The article presents information on human-provided services (HPSs) and human-based platforms in Web systems and closed enterprise systems. The set of issues that support the integration of human capabilities in service-oriented architecture such as designs, interaction patterns, reputation and discovery, are noted. It describes the HPS framework, which is made up of three layers, namely, data collection, services and middleware.